Tart cherry and pomegranate supplementations enhance recovery from exercise-induced muscle damage: a systematic review - Daniel Rojano Ortega; Antonio Molina López; Heliodoro Moya Amaya; Francisco Berral de la Rosa (Termedia Publishing House, 2020)
Phenolic compounds have antioxidant and anti-inflammatory properties and may prevent inflammation and oxidative stress as well as help the athletes to recover from exercise-induced muscle damage (EIMD). Tart cherry (TC) and pomegranate (PG) are two fruits with high content of polyphenols. Their antioxidant and anti-inflammatory properties have recently attracted substantial interest for their potential to reduce strength loss and promote recovery from EIMD. The aims of this review are (1) to summarise the effects of tart cherry and pomegranate supplementation on oxidative stress, inflammation and recovery, and (2) to outline the differences found in supplementation with tart cherries or pomegranates. SPORTDiscus, PubMed, Web of Science and Scopus were searched according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis and 25 studies were included. The existing evidence suggests that both types of supplementation are good strategies to accelerate recovery of functional performance variables, perceptual variables and inflammation but PG supplementation shows better recovery of oxidative stress. However, positive effects are more likely: 1) when supplementation starts some days before muscle damage is induced and finishes some days after, for a total period of at least 8/10 days, 2) with pronounced muscle damage of the muscles involved, and 3) when total phenolic content is at least 1000 mg/day. This review may help to optimise TC or PG supplementation practice to improve post-exercise recovery.